Critical perspectives on rehabilitation education, practice and process: northern Honduras case study - Valerie Umaefulam; Isabel Cristina Gómez-Díaz; Laura Marcela Uribe-Calderón; Eliany Pedrozo-Araque; Kalyani Premkumar; Ethel Maldonado-Molina; Maria Laura Basualdo; Julia Bidonde (BMC, 2022)
Abstract Background Rehabilitation services are an integral part of patient care, but in many developing countries, they are not prioritized and either unavailable or easily accessible to those who need them. Although the need for rehabilitation services is increasing in Honduras, rehabilitation workers are not included in the health care model that guides the care provided to communities, particularly in rural and remote areas. To understand the need for providing impactful rehabilitation services in disadvantaged communities, we explored the education and perception of the community relating to rehabilitation, investigated training available for rehabilitation workers, and examined the rehabilitation processes and practices in Northern Honduras from stakeholders' experiences. Methods We utilized a qualitative descriptive and interpretive approach grounded in case study methodology to understand rehabilitation education, process, and practice in Northern Honduras. Three rehabilitation centres were purposefully selected as the cases, and participants consisted of rehabilitation workers and managers from these centres. We collected data via interviews and focus group sessions. We analyzed the data via thematic analysis using NVivo version 12. Results In Northern Honduras, rehabilitation workers' limited training and continuing education, along with awareness about rehabilitation by community members and other health providers influence rehabilitation care. Although policies and initiatives to support people with disabilities and the broader community in need of rehabilitation exist, most policies are not applied in practice. The sustainability of rehabilitation services, which is rooted in charity, is challenged by the small range of funding opportunities strongly affecting rehabilitation care processes and clinical practices. The lack of trust and awareness from the medical profession towards rehabilitation workers sets a major barrier to referrals, interdisciplinary work, and quality of life for individuals in need of rehabilitation. Conclusion This study advances knowledge of the need to increase understanding of rehabilitation care among community members and health providers, improve care processes and resources, and foster interprofessional practice, to enhance the quality of care and promote equitable care delivery, especially in rural and remote communities.